Rekrutmen Pendidik Dan Tenaga Kependidikan Di SDN 036 Ujung Berung Kota Bandung - Ai Ina Afifah Munawwaroh; Dwi Ajeng Maulidya Makalao Maulidya Makalao; Muhammad Amar Khana (UIN Sunan Gunung Djati Bandung, 2023)
A common problem in recruiting teachers and education personnel in schools is the problem of plans for training teachers and educators who are not mature enough. Therefore the author wants to examine the purpose of this study, namely to find out how the planning, processes and strategies for recruiting educators and education staff at SDN 036 Ujung Berung, Bandung city, this research uses a qualitative approach. The method used for data collection is the Analytical Descriptive Method. In this research, the data collection method used was observation, interviews and documentation. Planning for Recruitment of Educators and Education Personnel at SDN 036 Ujung Berung, Bandung City Before recruiting prospective teachers and employers, the principal usually consults with teachers and staff to analyze their needs and determine the number of teachers and educators needed based on the needs analyzed. The strategy for recruiting new teachers at SDN 036 Ujung Berung, Bandung City, is as follows: Establishing a committee, determining requirements, freeing schedules, facilities needed for the recruitment process for new teachers. The process of recruiting new teachers is carried out selectively because recruitment is very important for the future of students and through the recruitment process schools can obtain quality human resources.